2013
DOI: 10.1590/s0004-27302013000700002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency is higher in patients with Paget's disease of bone compared with age-matched controls

Abstract: OBJECTIVE: To investigate if vitamin D deficiency is more prevalent in patients with Paget's disease of bone (PDB) than in age-matched controls. SUBJECTS AND METHODS: We measured serum 25-OHD in 28 untreated patients with PDB and two control groups: 284 elderly men from an ongoing cohort from our department, and 151 postmenopausal women seen in our outpatient clinic for routine medical evaluation. RESULTS: The mean ± SD serum 25-OHD was significantly lower in subjects with PDB (23.76 ± 6.29 ng/mL) than in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Several studies, including recent surveys in large patient cohorts, demonstrated that vitamin D deficiency (25OHD levels < 20 ng/ml) is frequent in PDB [ 126 , 131 , 132 ]. As previously outlined, N-BP treatment (particularly in case of potent intravenous compounds) may result in hypocalcemia that is more common in case of vitamin D deficiency.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…Several studies, including recent surveys in large patient cohorts, demonstrated that vitamin D deficiency (25OHD levels < 20 ng/ml) is frequent in PDB [ 126 , 131 , 132 ]. As previously outlined, N-BP treatment (particularly in case of potent intravenous compounds) may result in hypocalcemia that is more common in case of vitamin D deficiency.…”
Section: Results and Recommendationsmentioning
confidence: 99%
“…For patients with different diseases and receiving long-term medication, studies ( 63 65 ) showed that several drugs (e.g. antiepileptic agents, glucocorticoids, antiretroviral or anti-oestrogen drugs) interfered with vitamin D metabolism, which resulted in patients being more likely to have low vitamin D status.…”
Section: Human Intervention Studies On the Relative Effects Of Calcifmentioning
confidence: 99%